The implementation of live work sheet as digital media for student’s assessment - Lia Noviana; Citra Puteri Utami (IRecall Journal, 2024)
Live worksheet Live Worksheets is an application that helps teachers make material and questions more interactive with various activities like drag and drop, matching, multiple choice, etc. This application can be accessed online via a browser. Student’s assessment is an effort to obtain data or information, which is a process and result of learning to determine the quality or how well a student's performance is, the value of a class or course, or study program with certain criteria/learning outcomes or goals. This research is about The Implementation of Live Work Sheet as Digital Media for Student’s Assessment at the first semester of the seventh-grade students of SMPN 02 Bandar Lampung. The objective of this research is to describe process of student’s assessment by using live worksheet in teaching and learning process, the advantages, and disadvantages of using live worksheet in doing assessment. In this research, the researcher used descriptive qualitative research. The researcher used purposive sampling technique to determine the sample. The researcher chose class 7.10 (bilingual class) as sample which consisted of 30 students. In collecting the data, the researcher used three kinds of instruments, they are: observation, questionnaire, and document analysis. The researcher used three major of data analysis: they were data reduction, data display and conclusion drawing or verification. From the data analysis, the researcher found in The Implementation of Live Work Sheet as Digital Media for Student’s Assessment at SMPN 02 Bandar Lampung were as follows: The first, the student’s assessment by using live worksheet was running well, the classroom atmosphere was the students looked to understand in assessment but some of them looked less confused. The second, the students got some problems in doing assessment by using live worksheet, they were: the students felt the result was unfair and students thought that it was complicated. The third, the students got some benefit such as they can directly answer the question without write the whole text, they had much time in doing the test, and they can see the result directly. Hopefully, the result of the research will show that the implementation of live work sheet as digital media for student’s assessment will be useful for both. Finally, the teachers can directly assess the students work without checking one by one and the students can easily see their result after doing their work without having curiosity. Keywords: Digital Media, Implementation, Live Work Sheet, Student’s Assessment